Antibody kinetics and exposure to Toxoplasma gondii in cats: a seroepidemiological study. Issue 4 (March 2021) - Schreiber, Nora; Basso, Walter; Riond, Barbara; Willi, Barbara; Torgerson, Paul Robert; Deplazes, Peter
Graphical abstract: Highlights: Antibody kinetics were similar in cats inoculated with Toxoplasma gondii tissue cysts and oocysts. Naturally infected cats elicited a persisting humoral immune response against T. gondii . The Swiss cat population had a positive true T. gondii infection status of 42.4%. Male gender, age and outside access were associated with a higher risk for seropositivity. Abstract: Domestic cats are the most important definitive hosts for Toxoplasma gondii, the agent of an important global zoonosis. Serial sera from cats orally inoculated either with T. gondii tissue cysts ( n = 3) or sporulated oocysts ( n = 3) and from 65 client-owned cats, plus sera from 1, 757 client-owned cats presented to veterinarians in Switzerland were analysed for an antibody response to T. gondii by ELISA. Risk factors for seropositivity and prevalence were estimated with a generalised linear and beta regression model. The first model examined the association of an OD405 value as the dependent variable, with gender, age, and outside access as possible independent variables. In the second model, we first analysed the data assuming a bimodal distribution representing two overlapping distributions of OD405 values from positive and negative cats, enabling the assignment of a probability of true infection status to each cat. Mean probabilities of true infection status across groups represent an estimate of true prevalence. These probabilities were then regressed against age, gender and outside access. Antibody kinetics in cats orally inoculated with tissue cysts, shedding oocysts, did not differ significantly from those of cats inoculated with sporulated oocysts without detectable oocyst excretion, suggesting extraintestinal parasite invasion and exposure to tachyzoites in both situations at an early stage of infection. Analysis of serial serum samples suggested a persisting long-term humoral immune response. Of the client-owned cats, 42.4% (95% confidence interval (CI): 40.1–44.6) had a positive true infection status. This was higher (56.3% (95% CI: 53.2–59.6)) in cats with outside access than in those without (22.1% (95% CI: 18.9–25.4)). In the first model, the factors age ( P < 0.0001), gender (male: P = 0.046), and outside access ( P < 0.0001) were independently associated with significantly higher OD405 values. In the second model, the probability of having a positive true infection status increased with age ( P < 0.0001), was higher with outside access ( P < 0.0001) and in outdoor male cats ( P = 0.0006).